2021
DOI: 10.3389/fneur.2021.727962
|View full text |Cite
|
Sign up to set email alerts
|

Primary Brainstem Hemorrhage: A Review of Prognostic Factors and Surgical Management

Abstract: Primary brainstem hemorrhage (PBSH) is the most fatal subtype of intracerebral hemorrhage and is invariably associated with poor prognosis. Several prognostic factors are involved, of which the two most predominant and consistent are the initial level of consciousness and hemorrhage size. Other predictors, such as age, hyperthermia, and hydrocephalus, are generally not dependable indicators for making prognoses. Scoring systems have now been developed that can predict mortality and functional outcomes in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0
12

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(68 citation statements)
references
References 103 publications
(158 reference statements)
2
54
0
12
Order By: Relevance
“…In STIPE trial, we target critical patients with a score of 2-3 points who may benefit most from surgical management. 2 Hydrocephalus after PPH occurred in 30.3% of patients 19 which was identified as an independent prognostic factor of mortality. 20 To mitigate the possible impact of hydrocephalus on outcome assessment, we exclude the patients with initial hydrocephalus on admission which needs surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In STIPE trial, we target critical patients with a score of 2-3 points who may benefit most from surgical management. 2 Hydrocephalus after PPH occurred in 30.3% of patients 19 which was identified as an independent prognostic factor of mortality. 20 To mitigate the possible impact of hydrocephalus on outcome assessment, we exclude the patients with initial hydrocephalus on admission which needs surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In STIPE trial, we target critical patients with a score of 2–3 points who may benefit most from surgical management. 2 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brainstem involvement has been reported to be an independent predictor of mortality in sICH patients [4]. And if primarily involved, it is considered the most fatal location of ICH [13]. It has been reported before that a loss of ≥ 3 brainstem reflexes and the swirl sign on the baseline CT scan can be simple potential prognostic indicators of brain death for patients with ICH [4].…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…With the in-depth study of the anatomical structure and physiological function of the brainstem, it was confirmed that there is a relatively "safe operation area" in the brainstem [10][11][12]. Microsurgery is expected to become one of the most important ways to improve the prognosis of SHBSH patients [2,11].…”
Section: Introductionmentioning
confidence: 99%